Laboratory microcosm study of a polluted groundwater zone - Zsilinszky Ingrid; Kiss István; Mészáros Sándor; Fehér Balázs; International Symposium on Analytical and Environmental Problems (25.) (2019) (Szeged) (2019)
Microcosm studies were set up to predict and evaluate the most effective conditions for the bioremediation of a chlorobenzene contaminated groundwater zone. In the literature there are only few studies for chlorobenzene degradation under nitrate reducing circumstances. In most of our microcosms the indigenous groundwater bacteria were able to degrade this widespread recalcitrant compound under the new conditions. We have isolated a chlorobenzene degrading bacterium, Pseudomonas sp. EM1 which is capable of the mineralisation under aerobic and anaerobic conditions.